2016
DOI: 10.1111/apt.13634
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: development of hepatocellular carcinoma in chronic hepatitis B patients with hepatitis B surface antigen seroclearance

Abstract: Despite that HBsAg seroclearance can significantly reduce the risk for HCC, HCC can still develop in a proportion of CHB patient after HBsAg seroclearance. Closer attention should be paid to those patients with established cirrhosis or older age than 50 years at the time of HBsAg seroclearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 53 publications
5
79
0
Order By: Relevance
“…In patients chronically infected with hepatitis B virus (HBV), such seroclearance can occur after antiviral therapy, or, in 0.5%‐1% of patients per year, it can occur spontaneously . After HBsAg seroclearance, such patients may benefit from surveillance for hepatocellular carcinoma (HCC), as HBV can still be present at low replicative and transcriptional levels . In fact, HCC is the most frequent liver‐related complication after HBsAg seroclearance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients chronically infected with hepatitis B virus (HBV), such seroclearance can occur after antiviral therapy, or, in 0.5%‐1% of patients per year, it can occur spontaneously . After HBsAg seroclearance, such patients may benefit from surveillance for hepatocellular carcinoma (HCC), as HBV can still be present at low replicative and transcriptional levels . In fact, HCC is the most frequent liver‐related complication after HBsAg seroclearance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have already identified some patient characteristics that may be risk factors of HCC occurrence among patients who experience HBsAg seroclearance, such as cirrhosis, male gender and age ≥ 50 years . However, different studies disagree about some of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…There is less available data regarding the effect of the 3rd generation drugs, tenofovir and entecavir. One recent meta-analysis of patients with HBsAg seroclearance (n = 34,952) showed a significantly decreased risk for developing HCC in comparison to those with who did not seroconvert [risk ratio (RR) 0.34, 95% confidence interval (CI): 0.20-0.56, P < 0.001], but among those who seroconverted, 2.29% (95%CI: 1.19-4.37) still developed HCC [15] .…”
Section: Treatment Of Hbv and Hccmentioning
confidence: 99%
“…2 Liu et al conducted a meta-analysis of 28 smaller studies to overcome the limitations of insufficient statistical power common to studies evaluating the risk for HCC after HBsAg seroclearance. 3 Their results indicated that HBsAg seroclearance could be associated with a significant reduction in HCC risk; however, persons with HBsAg seroclearance were still at risk for HCC, especially those with established cirrhosis and aged >50 years. Jiang and colleagues presented an updated meta-analysis by eliminating duplicated studies from the analysis published by Liu et al 3 We commend their efforts, but we have two concerns with their alternative meta-analysis.…”
mentioning
confidence: 99%
“…3 Their results indicated that HBsAg seroclearance could be associated with a significant reduction in HCC risk; however, persons with HBsAg seroclearance were still at risk for HCC, especially those with established cirrhosis and aged >50 years. Jiang and colleagues presented an updated meta-analysis by eliminating duplicated studies from the analysis published by Liu et al 3 We commend their efforts, but we have two concerns with their alternative meta-analysis. First, Jiang and colleagues inferred the risk for HCC based on the pooled proportion of the participants who developed HCC across all of the studies.…”
mentioning
confidence: 99%